MENINGKATKAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) PADA SISWA KELAS VI SD AL-IRSYAD AL-ISLAMIYAH - Mangoda, Rusni (Universitas Khairun, 2024)
The aim of this research is to know the improvement of the result in learning process throught cooperative learning model number head together (NHT) for civic subject in SD Al-Irsyad Al-Islamiyah Kota Ternate. This research is conducted using qualitative approach with option classroom action reasearch (CAR). The scheme of activities consist of: (1) planning, (2) implementation, (3) observation, (4) reflection. In collecting of data used observation, test, and documentation, while, in Analysis the data, the researcher uses the technique in qualitative description analysis, the research object is the student in grade VI at SD Al-Irsyad Al-Islamiyah Kota Ternate.The result of the reaseach in cycle I, the students are stated get the standart minimum criteria about 30% or 16 students, in percentage average 60,9%, futhermore, in cycle II, the students has improved in standart minimum criteria in percentage 85% or 27 students with the scor value average 82,5%, the studentsâ€™ activities in cycle I get the average 50% and cycle II get average 82,69%.Â Next the teacher activity in cycle I get the average 53,57 and in cycle II get the average 83,92%.